The Correlation Between Emergency Medicine Residents’ Grit and Achievement - Olson, Adriana Segura (AEM Educ Train, 2019)
BACKGROUND: Early identification of emergency medicine (EM) residents who struggle with educational attainment is difficult. In‐training examination (ITE) scores predict success on the American Board of Emergency Medicine (ABEM) Qualifying Examination; however, results are not available until late in the academic year. The noncognitive trait “grit,” defined as “perseverance and passion for long‐term goals,” predicts achievement in high school graduation rates, undergraduate GPA, and gross anatomy. Grit‐S is a validated eight‐question scale scored 1 to 5; the average of responses represents a person’s grit. Our objective was to determine the correlation between EM resident Grit‐S scores and achievement, as measured by MCAT percentiles, ITE scores, and remediation rates. STUDY DESIGN AND METHODS: This was a 1‐year prospective, multicenter trial involving ten EM residencies from 2017 to 2018. Subjects were PGY‐1 to ‐4 EM residents. Grit‐S scores, MCAT percentile, remediation rates, ITE scores, and the ITE score’s prediction of passing the ABEM Qualifying Examination were collected. Correlation coefficients were computed to assess the relationship between residents’ grit and achievement. RESULTS: A total 385 of 434 (88.7%) residents participated who completed the Grit‐S as part of a larger study. The mean Grit‐S score was 3.62. Grit positively correlated with the predicted likelihood of passing the ABEM Qualifying Examination (r = 0.134, n = 382, p = 0.025). There was no correlation between grit and remediation (r = −0.04, n = 378, p = 0.46) or grit and MCAT percentiles (r =− 0.08, n = 262, p = 0.22). CONCLUSIONS: The positive correlation between Grit‐S scores and percent likelihood of passing the ABEM Qualifying Examination demonstrates grit’s potential to assist residency leadership in early identification of residents who may attain a lower ITE score.